Predictive factors of successful endovascular recanalization for symptomatic atherosclerotic non-acute middle cerebral artery occlusion - Ma, Lin; Zhang, Hao; Yan, Shuo; Bai, Weixing; Zhang, Yingqiang; Wu, Dedi; Du, Jiahang; Lu, Zhiyong; Tan, Huaqiao (Frontiers in Neurology, 2025)
BackgroundEndovascular recanalization treatment (EVRT) has emerged as a critical treatment modality for patients with symptomatic atherosclerotic non-acute middle cerebral artery occlusion (SNMCAO). However, several technical challenges persist, and the predictive factors for successful recanalization of SNMCAO are not yet fully understood. This study aimed to identify clinical and radiological factors associated with successful EVRT in patients with SNMCAO.MethodsWe conducted a retrospective analysis on all patients with SNMCAO who underwent EVRT at two centers from January 2016 to December 2024. Demographic data, medical history, imaging characteristics, periprocedural complications, and 3-month follow-up results were collected. Logistic binary regression analysis was performed to assess the factors influencing the success of EVRT.ResultsA total of 65 patients were included, with 50 achieving successful recanalization. The perioperative complication rate was 13.8% (9/65). Multivariate logistic binary regression analysis indicated that an occlusion duration of ≤ 3 months (P = 0.020), an occlusion segment length of ≤ 10 mm (P = 0.004), the presence of a distal vascular main trunk visualization (DVMTV) sign (P = 0.035), and the presence of a slow distal antegrade flow (SDFA) sign (P = 0.039) were identified as independent positive predictors of successful EVRT for SNMCAO.ConclusionOcclusion duration of ≤ 3 months, occlusion length of ≤ 10 mm, the presence of a DVMTV sign and a SDFA sign were considered independent predictive factors for the success of EVRT in patients with SNMCAO.